Monotonic Preferences and Core Equivalence - Manelli, Alejandro M. (Econometrica, 1991)
MONOTONICITY OF PREFERENCES is a common assumption in the theory of the core of an economy. It implies that any increase in consumption will be welcomed by a consumer, independent of the reference consumption bundle. Although it seems to be an innocuous assumption, there are several important instances in which monotonicity is not satisfied. The simplest one embraces commodities or services that some economic agents dislike. A second failure of monotonicity is given by satiation points. Many goods may increase the consumer's welfare up to a point, but become a burden if consumed in excess. Goods that must be consumed in fixed proportions constitute yet another exception to the monotonicity assumption. Coffee and cream, and cars and tires are typical examples. In this paper we shall study the relationship between core allocations and the set of competitive equilibria when preferences are not monotonic.